The substitutability of labor of selected ethnic groups in the US labor market - Martin Kahanec (Institute for the Study of Labor (IZA), 2006)
This paper investigates the substitutability of labor of selected ethnic groups in the US labor market. In the generalized Leontief framework, the analysis of US census-based data reveals that labor of non-White ethnic groups is complementary to that of White ethnic group. This finding supports the view that the negative relationship between the relative earnings of an ethnic group and its relative size is a labor market phenomenon. Moreover, it implies that ethnic diversity of labor force has positive effects on aggregate output. While the estimated elasticities of complementarity are relatively small, they are shown to generate significant effects, given the very uneven distribution of ethnic groups across local labor markets, as resulting from long-run migration patterns.
Keywords: J15; J24; 330; substitutability; elasticity of substitution; ethnic group; labor market